Ideographic usage of "choice" in contemporary abortion rhetoric - Snider, Sarah Jane (Kansas State University, 2008)
This work explores the emergence and evolution of the rhetoric choice rhetoric as it pertains to contemporary American abortion politics. is explored from an ideographic perspective, borrowing from the theoretical framework for ideographic rhetorical criticism established by Michael Calvin McGee. The analysis begins with a diachronic analysis of the emergence of the ideograph of within the law with an investigation of the written decisions in four Supreme Court cases central to the construction of the right to choose: Roe v. Wade (1973), Maher v. Roe (1977), Harris v. McRae (1980), and Webster v. Reproductive Health Services (1989). This investigation reveals a synchronic relationship between and another higher order ideograph, . The criticism continues with an investigation of the usage of by pro-choice advocates in two documents published by NARAL Pro-Choice America, Choices: Women Speak About Abortion is a collection of women's narratives about their experiences obtaining an abortion, and Breaking Barriers, a guide for the development and implementation of proactive policy campaigns for pro-choice advocates. McGee's method is employed to investigate the ideographic usage of within these documents, revealing the ideographic abstraction that associates the alleged idea content of ideographs. This ideographic analysis reveals the inability of to live up to its alleged idea content as a result of the limitations inherent in the grounding of within the higher order ideograph of and the impact of these limitations on particular populations, mainly indigent women in the United States.
Keywords: Ideograph; Choice; Abortion; Pro-Choice; Speech Communication (0459)